1997
DOI: 10.1093/ajcp/107.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Papanicolaou Smear Sensitivity for Adenocarcinoma In Situ of the Cervix:A Study of 34 Cases

Abstract: The sensitivity of cervical smears for adenocarcinoma in situ (AIS) is not known, nor is it known whether false-negative smears are due to sampling or to screening or interpretive errors. In 16 of 34 patients with AIS, 38 negative smears were reported 2 weeks to 7 years before biopsy. Thirty-one of these negative smears were rescreened, and 17 (55%) were retrospectively diagnosed as abnormal. The purpose of this study was to obtain an estimate of Pap smear sensitivity for AIS and to uncover difficulties in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 13 publications
1
59
0
Order By: Relevance
“…However, those studies varied in their definition of a positive outcome and in the time interval between cytology and positive histology. 5,15,16 Schoolland et al, 5 using methods similar to our own, reported that 'high-grade' sensitivities at 2 different centers were 48% and 54% using conventional PS only.…”
Section: Discussionsupporting
confidence: 55%
“…However, those studies varied in their definition of a positive outcome and in the time interval between cytology and positive histology. 5,15,16 Schoolland et al, 5 using methods similar to our own, reported that 'high-grade' sensitivities at 2 different centers were 48% and 54% using conventional PS only.…”
Section: Discussionsupporting
confidence: 55%
“…This finding is at least as good as in other recent series. 17,18 We conclude that AIS is predominantly a screen-detected disease and are encouraged by the earlier mean age at diagnosis as compared with earlier studies. A decline in the incidence of invasive adenocarcinoma may be expected in the near future.…”
Section: Mitchell Et Almentioning
confidence: 67%
“…21 To determine the sensitivity of the Papanicolaou smear for diagnosing CVCA and to characterize sources of false-negative diagnoses, we conducted a retrospective review of the Papanicolaou smear findings from 49 patients with CVCA.…”
Section: Resultsmentioning
confidence: 99%